[BP.08.07] RESIDENT STEM CELLS IN THE PERIVASCULAR ADIPOSE TISSUE IS ALTERED DURING AGING. (September 2017) - Gao, P.
Abstract : Objective: The presence of a range of multipotent stem cells in the adventitia of the vessel wall has been identified. However, the resident stem cells in the perivascular adipose tissue (PVAT) is poorly understood in vascular disease. This study aims to characterize the resident PVAT-derived stem cells (PVASCs) and investigate their fate in the vascular remodeling process during aging. Design and method: PVASCs obtained from the PVAT of mice were characterized by flow cytometry and immunostaining for mesenchymal stem cell (MSC) markers. In vivo, the differential potential of PVASCs was evidenced by matrigel coated PVASC delivery to the perivascular tissue after ligation injury of carotid arteries. PVASCs obtained from patients who underwent coronary artery bypass grafting surgery were also characterized by flow cytometry and immunostaining for mesenchymal stem cell (MSC) markers. Results: PVASCs showed multiple differentiation capacity towards endothelial cells, smooth muscle cells, osteoblasts and adipocytes. It is worth noting that aged PVASCs showed a depressed differential ability towards multiple potential cells. In vivo, coated aged PVASCs accelerated vascular remodeling compared with young cells, accompanied by reduced differentiation of endothelial cells and perivascular brown adipocytes, and high motility towards myofibroblasts. Moreover, PVASCs obtained from patients who underwent coronary artery bypass grafting surgery also showed expression of typical stem cell markers, CD90 and CD29, as well as higher induction of vascular disease in nude mice after ligation injury. Conclusions: Taken together, our study is the first report to characterize the resident stem cells in situ from PVAT. The multiple differentiation capacity of PVASCs is altered during aging and participates in the vascular remodeling process.